Rzymska koncepcja darowizny na wypadek śmierci w komentarzu Paulusa do lex Iulia et Papia (D. 39.6.35.2–3) - Sobczyk, Marek (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> The most important feature of the Roman donatio mortis causa was its potentially returnable character. This donation was applied in diff erent forms. In its basic form it consisted in gratuitous transfer of ownership to the donee motivated by the imminent danger to donor’s life. Donor could claim the recovery of the donation if the danger to his life ceased to exist or the donee died. In the postclassical law another form was recognized, namely donation motivated by the sole contemplation of death, that means without any requirement of the imminent danger to donor’s life or other particular circumstances. The donor’s aim was on one hand that after his death the subject of the donation would belong to the donee, not to the heirs, and on the other hand that he would be able to reclaim it if the danger to his life ceased to exist. Donatio mortis causa became perfect, that means took full eff ect, after the donor’s death provided that the donee was still alive at that time. This form of donation was applied to circumvent the restrictions of Roman inheritance law, especially those related to certain groups of persons. In the course of development of law donation mortis causa was gradually assimilated to the institutions of inheritance law and fi nally in Justinian’s law it was equalized with legacies. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->